Contemporary research and analysis on the children of prisoners : invisible children - Gordon, Liz, 1955- (Cambridge Scholars Publishing, 2018)
From back of book :" The papers in this collection cover many of the themes in the wider literature on the children of prisoners. Advocacy themes include moving towards child-friendly prison systems, using mass incarceration to influence wider social change, the effects of pre-trial detention on families, the particular issues in Hawaii and how detention procedures harm children